Architecture of the multi‐functional SAGA complex and the molecular mechanism of holding TBP. (29th September 2020) - Ben‐Shem, Adam; Papai, Gabor; Schultz, Patrick
Abstract : In eukaryotes, transcription of protein encoding genes is initiated by the controlled deposition of the TATA‐box binding protein TBP onto gene promoters, followed by the ordered assembly of a pre‐initiation complex. The SAGA co‐activator is a 19‐subunit complex that stimulates transcription by the action of two chromatin‐modifying enzymatic modules, a transcription activator binding module, and by delivering TBP. Recent cryo electron microscopy structures of yeast SAGA with bound nucleosome or TBP reveal the architecture of the different functional domains of the co‐activator. An octamer of histone fold domains is found at the core of SAGA. This octamer, which deviates considerably from the symmetrical analogue forming the nucleosome, establishes a peripheral site for TBP binding where steric hindrance represses interaction with spurious DNA. The structures point to a mechanism for TBP delivery and release from SAGA that requires TFIIA and whose efficiency correlates with the affinity of DNA to TBP. These results provide a structural basis for understanding specific TBP delivery onto gene promoters and the role played by SAGA in regulating gene expression. The properties of the TBP delivery machine harboured by SAGA are compared with the TBP loading device present in the TFIID complex and show multiple similitudes. Abstract : TATA‐box binding protein orchestrates transcription initiation when deposited onto the promoter of protein coding genes. The structure of the SAGA co‐activator reveals how TBP is held within the 19‐subunit complex and prevented to interact with spurious DNA. A deformed octamer of histone fold proteins establishes a TBP binding interface driven by the Spt3 subunit. The action of the general transcription factor TFIIA is required to dislodge TBP from SAGA and load it onto the promoter.